(untitled) (Journal of the College of Education for Women, 2019)
A- The research problem: the research problem which is the garments industry, as awhole it does not rely on a single system in the sizes of the clothing and the workingcompanies, see that it is not plausible that the sizes be unificd and consistent in all companies.The current sizes in the domestic Iraqi markets are not suitable for some females ,on the otherhand the Iraqi industry suffers the lack of a modern standard for some Iraqis female bodies.B- The Signifiance of the research: lies in the study of the diversity of the human bodysizes and naming them to reflect the desires and requirements of the consumer and try to finda method to meet their expectations as well as to raise the level of garments industrysupported by modern technology and then to the issuance of Iraqi fashion magazines.C- The research aim: Find a standard for the Iraqi woman’s body to a selected category(19-24 years).D- The samples study: which included (500) students of the third class of the college ofScience and Education for women of (19-24years). The students were selected randomly afterexcluding married women; The main experiment done in the colleges sites to reduce time andeffort which lasted for three month. The experiment includes taking the bodies measurementsof the samples examined .The research restricted for only on (21) body size.E- Research Results:Estimations of the standard statistics of the studied variables:The trimmed average value is not fundamentally different as the arithmetic average value,which reflects that the arithmetic average value does not affected by the existence of extremeand anomalies value that came in some of old people of the studied sample as well as thevalue of the interquartile range achieved a low level which reflected a high degree ofhomogeneous of the studied variables in general.